Understanding Intersectionality through Tequila Leila’s Experience in 10 Minutes 38 Seconds in this Strange World (2019) - Wandira, Diah Putri Ayu; Datau, Rizal Octofianto; Wulan, Nur (POETIKA, 2023)
The article aims to explore intersectionality and its societal impact on the characters as portrayed in Elif Shafak’s 10 Minutes 38 Seconds In This Strange World (2019). This issue was extensively discussed to comprehend the representation of gender inequality and patriarchy in the story. Although the text has been the subject of discussion among a limited number of scholars, the novelty of this study lies in its adoption of a theoretical perspective that has not been utilized previously, specifically Kimberly Crenshaw’s framework of intersectionality. Methodologically, this qualitative study identified and collected the primary data from the text by selecting direct and indirect quotations relevant to the issue discussed. This approach was complemented by secondary sources from previous and related studies which were drawn from books and journal articles. Having analyzed the text by applying Crenshaw’s theory of intersectionality, the authors found that Shafak represented gender inequality and patriarchy in Turkey as a hegemonic and systematic belief. The text also discovered that the perpetuation of the patriarchal system, rooted in the practices frequently justified by religious rhetoric, is effectively prolonged by the continued male dominance in shaping public policies. It also indicates that the main character, Tequila Leila, and the other characters in the story possess overlapping identities, leading to numerous unfortunate experiences. Tequila Leila’s oppressed experiences unveiled the structural and representational intersectionalities.